Die unzulässige Substitution des chefärztlichen Behandlers und ihre Auswirkungen - Weise, Claas-Thorge (Universitätsverlag Göttingen, 2022)
It is common practice for patients in a hospital to be treated by the on-duty physician. If patients want to be treated by a certain physician, then they are subject to additional charges. This is referred to as 'chief physician treatment' because it is often chief physicians who are selected to carry out treatment. Commonly, chief physicians are considered to be particularly experienced and competent. But even if a chief physician treatment is contractually agreed with the patient, in many cases it is not the chief physicians who provide the individual treatment services. Sometimes they do not even participate in the treatment at all but nevertheless all the services are billed as chief physician treatment. Whether and the extent to which the law allows this kind of practice, is the subject of this dissertation.